Consumers Count : How Water and Sanitation Utilities Can Become More Accountable to Their Users - Muller, Mike; Simpson, Robin; Ginnekan, Meike van (World Bank, Washington, DC, 2012)
This note presents tools that can help make service providers more accountable to the people they serve. The voice of users is often muted in water utilities. One consequence is that utilities do not take account of users' priorities and preferences. The utility, in turn, loses the trust and cooperation of the community that it is supposed to serve. The result is often service deterioration, further alienating users. Traditionally, users relied on politicians to maintain oversight of budgets and compliance with rules and to intervene on their behalf when services failed. This institutionalized a long route of accountability from user to political representative to service provider. Modern approaches to public management seek to hold service providers more directly accountable to their users for the outcomes of their work. Providers are expected to ensure that water flows safely and reliably from taps, that blocked drains are cleared, and that services are accessible and affordable to all. Accountability in this context is about establishing a direct short route between users and service providers. Tools for accountability cannot by themselves provide sustainable water services. But their use can contribute to this goal, by improving utility practices and the utility's policy and institutional environment.